A propagação de notícias falsas via internet e suas implicações jurídicas - Oliveira, Giovana Coimbra de (Universidade Federal do Tocantins, 2020)
This paper studies the problematics of disinformation on the internet. Through an analysis of the historical and sociological context of the evolution of means of information spread and how the information disorder influences democracy, it aims to understand what are the legal implications of fake news sharing through world wide web. This research presents itself as inductive and qualitative, using the historicalevolutionary research method, combined with the comparative method and historical facts related to this issue, as well as recent news relevant to the subject. A bibliographic research was conducted based on doctrines, articles, theses, dissertations and journals found through the digital platforms of CAPES, USP and Google Scholar. It reached the understanding that it is necessary a better regulation about the dissemination of information on the internet in order to avoid society from feeling insecure when accessing information through this mean.